Clinical outcomes of a fenestrated frozen elephant trunk technique for acute type A aortic dissection. (7th December 2020) - Okamura, Homare; Kitada, Yuichiro; Miyagawa, Atsushi; Arakawa, Mamoru; Adachi, Hideo
Abstract: : OBJECTIVES: We investigated the outcomes of a fenestrated frozen elephant trunk (FET) technique performed without reconstruction of one or more supra-aortic vessels for aortic repair in patients with acute type A aortic dissection. METHODS: We investigated 22 patients who underwent the fenestrated FET technique for acute type A aortic dissection at our hospital between December 2017 and April 2020. The most common symptom was chest pain and/or back pain. Nine patients presented with malperfusion and 1 with cardiac arrest, preoperatively. A FET was deployed under hypothermic circulatory arrest and manually fenestrated under direct vision. Single fenestration was made in the FET in 15 patients, 2 fenestrations in 5 patients and a total fenestrated technique in 2 patients. Concomitant procedures were performed in 5 patients. RESULTS: The cardiopulmonary bypass, aortic cross-clamp and hypothermic circulatory arrest times were 181 ± 49, 106 ± 43 and 37 ± 7 min, respectively. In-hospital mortality, stroke, or recurrent nerve injury did not occur in any patient. One patient developed paraparesis, which completely recovered at discharge. During the follow-up period (mean 18 ± 7 months), 1 patient died of heart failure. Fenestration site occlusion did not occur. Follow-up computed tomography (mean 12 ± 6 months postoperatively) revealed that the maximal aortic diameter remained unchanged at the levels of the distal end of the FET, the 10th thoracic vertebra and the coeliac artery; however, the aortic diameter was significantly reduced at the level of the pulmonary artery bifurcation. CONCLUSIONS: The fenestrated FET technique is a simple, safe and effective procedure for selected patients with acute type A aortic dissection.